Pendidikan Jasmani Solusi Atasi Kecanduan Gadget - Fatkhur Rozi (Asatiza: Jurnal Pendidikan, 2021)
Gadgets are the technological developments created through sophisticated previous devices with more practical goals and functions. The development of gadgets provides convenience and effectiveness of the work that a person does. On the other hand, it also has a negative impact if use is not under control. The existence of gadgets is not only used by adults but also by adolescents and children. Uncontrolled and excessive use of gadgets can lead to addiction at the age of children and impact children's development, such as emotional and behavioral disorders, lack of movement that triggers health problems and triggers individualistic attitudes. This study aimed to solve gadget addiction through the implementation of good physical education in schools. This study was a qualitative study with a scientific review approach. The results provided an overview of the formation of good character, growth of social values that exist during physical education to prevent the younger generation being addicted to gadgets.